Pupil dilation response elicited by violations of auditory regularities is a promising but challenging approach to probe consciousness at the bedside - Aude Sangare; Marion Quirins; Clémence Marois; Mélanie Valente; Nicolas Weiss; Pauline Perez; Amina Ben Salah; Esteban Munoz-Musat; Sophie Demeret; Benjamin Rohaut; Jacobo D. Sitt; Cecile Eymond; et al. (Scientific Reports, 2023)
Abstract Pupil dilation response (PDR) has been proposed as a physiological marker of conscious access to a stimulus or its attributes, such as novelty. In a previous study on healthy volunteers, we adapted the auditory “local global” paradigm and showed that violations of global regularity elicited a PDR. Notably without instructions, this global effect was present only in participants who could consciously report violations of global regularities. In the present study, we used a similar approach in 24 non-communicating patients affected with a Disorder of Consciousness (DoC) and compared PDR to ERPs regarding diagnostic and prognostic performance. At the group level, global effect could not be detected in DoC patients. At the individual level, the only patient with a PDR global effect was in a MCS and recovered consciousness at 6 months. Contrasting the most regular trials to the most irregular ones improved PDR’s diagnostic and prognostic power in DoC patients. Pupillometry is a promising tool but requires several methodological improvements to enhance the signal-to-noise ratio and make it more robust for probing consciousness and cognition in DoC patients.